2018
DOI: 10.1007/s10103-018-2524-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meta-tetrahydroxyphenylchlorin photodynamic therapy on isogenic colorectal cancer SW480 and SW620 cells with different metastatic potentials

Abstract: The aim of this study is to investigate the antitumor effects and possible mechanisms of meta-tetrahydroxyphenylchlorin-mediated photodynamic therapy (m-THPC-PDT) on human primary (SW480) and metastatic (SW620) colon cancer cell lines. SW480 and SW620 cells were incubated with various concentrations of m-THPC, followed by photodynamic irradiation. Subcellular localization of m-THPC in cells was observed with confocal laser scanning microscopy (CLSM). Photocytotoxicity of m-THPC in the two cells was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…The first obvious answer is that PDT, in principle, may be effective against some cancers, based on results of experiments in-vitro, rodent models, and clinical studies. Examples of cancers, where encouraging results with PDT have been obtained in-vitro include breast cancer [11], oesophageal cancer [12], liver carcinoma [13], and colorectal cancer [14]. Further information on in-vivo application of PDT can be found elsewhere [15].…”
Section: Development Of the Concept Of Pdtmentioning
confidence: 99%
“…The first obvious answer is that PDT, in principle, may be effective against some cancers, based on results of experiments in-vitro, rodent models, and clinical studies. Examples of cancers, where encouraging results with PDT have been obtained in-vitro include breast cancer [11], oesophageal cancer [12], liver carcinoma [13], and colorectal cancer [14]. Further information on in-vivo application of PDT can be found elsewhere [15].…”
Section: Development Of the Concept Of Pdtmentioning
confidence: 99%
“…M-THPC and VP are two second-generation photosensitizers: m-THPC has been mainly used in the treatment of patients with head and neck cancer, while VP has been primarily used in the treatment of patients with age-related macular degeneration 40 , 41 . Recently, evidence has shown that m-THPC and VP exhibited excellent antitumor efficiency in CRC cells 16 , 42 . In this study, we found that m-THPC-PDT and VP-PDT had a strong phototoxic effect on CRC cells, as shown by decreased cell viability and increased ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…PSs function as catalysts during the process of PDT 15 . Meta-tetrahydroxyphenylchlorin (m-THPC) and verteporfin (VP) are second-generation photosensitizers that exhibit considerable photocytotoxicity to various tumor cells 16 , 17 . Emerging studies have found that m-THPC-PDT and VP-PDT could be promising therapeutic candidates for the treatment of human cancers 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…2,10 CRC arises from benign adenomatous polyps in the colon. 1,2 When polyps become cancerous, they become full-blown tumors on the wall of the colon and later protrude outwards into the intestinal lumen. 11,12 These outward protruding tumors can then also spread further into the cardiovascular or lymphatic system, as well as to other tissues or organs of the body, resulting in secondary cancer metastasis.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Colorectal cancer (CRC) frequently emerges from precancerous polyps that are initially conned in the innermost mucosal layers of the colon. 1,2 This devastating disease is recognized amongst the most prevalent malignancies and can be considered as the second leading cause of tumor-associated deaths in women and the third most common in men worldwide. 3 Recent projections have indicated that by 2030, the incidence and mortality rate of CRC will increase by 60% globally.…”
Section: Introductionmentioning
confidence: 99%